THE INFLUENCE OF LEADERSHIP STYLE, WORK DISCIPLINE AND COMPETENCE TO EMPLOYEE PERFORMANCE IN PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Zuwita Winasari Sitanggang; Fariza Fitria; Nelin Pricilia Simatupang (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study is intended to explore how the influence of leadership style, work discipline level, and employee competence on work performance within PT. Nusantara III Plantation (Persero) Medan. Using a quantitative approach, data was obtained through the distribution of questionnaires to 106 employees as research participants. The findings of the study indicate that a leadership style that creates an open communication space, involves employees in the work process, and provides consistent guidance, is able to build a more productive work atmosphere. High work discipline can be seen from adherence to company procedures, accuracy in completing responsibilities, and compliance with internal regulations also show a close relationship with improving individual performance. These three aspects, when carried out synergistically, play an important role in encouraging the effectiveness of employee work in the organization. Meanwhile, competencies, which include technical skills, mastery of science, and professional work attitudes, have proven to be important drivers in supporting employee effectiveness. This research provides input for the management of PT. Perkebunan Nusantara III (Persero) Medan to continue to strengthen adaptive and humanist leadership capacity, encourage the creation of a culture of discipline in the work environment, and provide continuous training to improve the competence of human resources.